Design and development of a tilt-wing UAV - Cetinsoy, Ertugrul; Sirimoglu, Efe; Oner, Kaan Taha; Hancer, Cevdet; Unel, Mustafa; Aksit, Mahmut Faruk; Kandemir, Ilyas; Gulez, Kayhan (Tubitak Scientific & Technological Research Council Turkey, 2011)
In this paper: the mechanical and aerodynamic design, carbon composite production, hierarchical control system design and vertical flight tests of a new unmanned aerial vehicle ( U AV), which is capable of VTOL (vertical takeoff and landing) like a helicopter and long range horizontal flight like an airplane, are presented. Real flight tests show that the aerial vehicle can successfully operate in VTOL mode Kalman filtering is employed to obtain accurate roll and pitch angle estimations.
Keywords: UAV; quad tilt-wing; VTOL; IMU; Kalman filter; Computer Science; Engineering